PELATIHAN PEMBUATAN PAKAN TERNAK DENGAN PEMANFAATAN SARANA BUMDES BERSAMA BAGI KELOMPOK USAHA KAWASAN PEDESAAN - Ria Harmayani; Abyadul Fitriyah; Yuni Mariani; Ni Made Andry Kartika; Nefi Andriana Fajri; Lalu Moh. Nazar Fajri; Muhammad Sohibul Ihsan; Sukran Makmun (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Islam Indragiri, 2021)
Utilization of local feed resources aims to encourage the independence of farmers in meeting the needs of feed ingredients and their processing. The independence of farmers can be supported by maximizing livestock farming and collaborating with BUMDes in order to create an increase in the economic welfare of livestock business groups in rural areas. the use of BUMDes together for livestock business groups in rural areas provides a forum for breeders and BUMDes management to continue to develop businesses, especially livestock businesses. It is hoped that the development of livestock business at the joint BUMDes in Aikmel District can minimize the low productivity of livestock and the use of local feed raw materials in rural areas, so that the joint BUMDes continue their business and farmers can more easily get the transfer of knowledge of feed technology and feed supplements in efforts to increase livestock productivity. The stages in this service include observation, planning, follow-up and evaluation. The training implementation methods are lectures and direct practice, question and answer and discussion methods. Based on the results of the training, it shows that the participants have been able to carry out management and management of livestock business units in their respective livestock groups, which can be seen from the training and mentoring carried out by the resource persons.